San Francisco Housing - Mark Banholzer; Paul Griesemer (Oz, 1985)
Recent studies and statistics provided by the 1980 Census indicate a significant and increasing percentage of people in the United States now living as members of non-traditional, professional households. The economic and social conditions which have produced this trend also suggest changes in the form of housing that we build...